PENGUASA, PENGUSAHA, DAN PETANI: Kapitalisme Perkebunan Sawit, Distorsi Sosial Ekonomi, dan Perlawanan Petani di Indragiri Hulu, Riau, 1978–2010 - Zaiyardam Zubir (Masyarakat Indonesia, 2017)
The main subject of this research is about the practice of modern capitalism in form of large scale of oil palm plantation and the peasant resistance in the Indragiri Hulu, Riau. It started from the government policy to expand non-oil and gas industry. The local government in Riau responded the policy by allowing big entrepreneurs to invest their capital in plantation economy, and the palm oil plantation was the main form. The main question raised in this study is why the peasant society in Indragiri Hulu resisted the practice of plantation economy in this area. This study employs historical method by using primary and secondary sources. The primary sources mainly derived through oral historical method and secondary source colleted from various libraries in Pekanbaru, Rengat, Yogyakarta, and Jakarta. The important finding of this research is that the expansion of plantation capitalism in Indragiri Hulu created various problems, especially land issues, as low ompensation and land grabbing. The authority and the  businessmen also ignored local tradition related to land ownership like ulayat land, traditional arable forest and protected forest. This caused two form of resistant, closed and opened resistance. This research concludes that the practice of modern plantation based on traditional social and economic system triggered various anomalies They are includes: first, the weakening local community’s rights of land. Second, the violation of customry law by the capital owners especially those related to land. Third, the appearance of brokers that disadvantaged the peasant. Fourth, unbalanced relationships between the authority, the businessmen and peasant. Fifth, the emergence of peasant resistance against capitalism practice. Sixth, the rise of new sub-urban around the plantation.Keywords: authority, entrepreneur, peasant, resistance, plantation, palm oil ABSTRAKPermasalahan pokok penelitian ini adalah tentang perlawanan petani perkebunan sawit di Indragiri Hulu, Riau. Perlawanan petani ini tidak terlepas dari kebijakan nasional yang mendukung ekspansi industri non-migas. Usaha nonmigas yang dikembangkan pemerintah pusat adalah pembukaan perkebunan besar. Pembukaan perkebunan besar membutuhkan tanah yang luas sehingga investor mengembangkan usahanya sampai ke pelosok-pelosok seperti di Indragiri Hulu. Pengembangan perkebunan sawit itu membawa persoalan dalam masyarakat dan perlawanan petani. Studi ini mengkaji praktik kapitalisme perkebunan dan perlawanan masyarakat, khususnya petani di Indragiri Hulu.  Penulisan ini menggunakan metode sejarah dengan menggabungkan antara sumber tertulis dan sumber lisan, baik  primer maupun sekunder. Ekspansi kapitalisme perkebunan di Indragiri Hulu menimbulkan berbagai persoalan, terutama masalah tanah, seperti ganti rugi yang rendah dan perampasan tanah. Penguasa dan pengusaha juga mengabaikan nilai-nilai lokal menyangkut kepemilikan tanah, seperti tanah ulayat, hutan adat, dan hutan larangan. Hal ini menyebabkan munculnya dua bentuk perlawanan petani, yaitu tertutup dan terbuka. Kesimpulan yang dapat diambil dari penelitian ini adalah praktik kapitalis perkebunan yang didasarkan pada sistem ekonomi tradisional menimbulkan berbagai anomali dalam masyarakat, khususnya di kalangan petani. Anomali itu di antaranya, pertama, melemahnya hak atas kepemilikan tanah dari penduduk lokal (asli). Kedua, berlangsungnya pelanggaran terhadap hukum adat, terutama menyangkut tanah oleh pemilik modal. Ketiga, munculnya broker-broker yang merugikan petani. Keempat, terjadinya unbalanced relationships atau relasi yang tidak seimbang antara penguasa, pengusaha, dan petani. Kelima, perlawanan petani terhadap praktik kapitalisme di Indragiri Hulu. Keenam, adanya efek samping berupa kemunculan sub-sub-urban di pinggiran perkebunan besar.Kata kunci: penguasa, pengusaha, petani, perlawanan, perkebunan, sawit